Implementation of Islamic Religious Education Learning for Children with Special Needs at Al-Azhar Elementary School Kota Bukittinggi - Suharjo, Suharjo; Hanani, Silfia; Jasmienti, Jasmienti (Jurnal Pendidikan Agama Islam, 2020)
The segregation education system is starting to be abandoned and shifting to an inclusive education system. The inclusive education system is to unite children with special needs (ABK) with children without special needs (ATBK) in the same class they interact with, communicate and learn together. This research uses descriptive qualitative research with data collection obtained from observations, interviews, and documentation. The implementation of Islamic religious education learning for students with special needs at SD Al-Azhar Bukittinggi unites ABK students with ATBK in a fully inclusive classroom under the supervision of class teachers and special companion teachers (GPK). The implementation of Islamic Religious Education learning for children with special needs through inclusive education at SD Al-Azhar Bukittinggi students with special needs assisted by a striking companion teacher has a better understanding of the subject matter than ABK without a special companion teacher.